Drama pedagogy and the core competency development of pre-service teachers: the mediating and moderating roles of psychological well-being - Hu, Yaxin; Shu, Jack (Frontiers in Education, 2025)
This study examines how drama pedagogy supports core competency development among Chinese pre-service teachers, focusing on the mediating and moderating roles of psychological well-being. Grounded in positive psychology and social–emotional learning (SEL), a convergent mixed-methods design combined quantitative analyses (t-tests, structural equation modeling (SEM), and moderated regression) with qualitative focus groups. Participants were vocational college students who were divided into an experimental group receiving a drama-integrated curriculum and a control group with traditional instructions. The results showed that drama pedagogy significantly enhanced communication, collaboration, critical thinking, creativity, and cultural awareness. Psychological well-being fully mediated these effects, while moderation was non-significant. The qualitative findings revealed emotional catharsis, peer support, and embodied collaboration as mechanisms for growth. The study reconceptualizes well-being as an active pedagogical force, highlights the value of mixed methods, and suggests embedding structured drama and well-being support into teacher education. Implications extend beyond China to international debates on arts-based pedagogy.